THE SOCIAL SIGNIFICANCE OF POLITICAL PARTIES ROLE IN ENHANCING THE SPIRITUAL POTENTIAL OF YOUTH - Rakhmatova, Mekhrinoz (Oriental Journal of History, Politics and Law, 2025)
This article extensively examines the social significance of political parties role in enhancing the spiritual potential of youth. The functions of political parties in shaping the spiritual world of young people are critically analyzed. The research methods employed in this article include analysis, synthesis, comparative analogy, and generalization. Additionally, special attention is given to the harmony between politics and spirituality in the worldview of young people.